Chemicals to enhance microalgal growth and accumulation of high-value bioproducts - Yu, Xinheng; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2015)
Photosynthetic microalgae have attracted significant attention as they can serve as important sources for cosmetic, food and pharmaceutical products, industrial materials and even biofuel biodiesels. However, current productivity of microalga-based processes is still very low, which has restricted their scale-up application. In addition to various efforts in strain improvement and cultivation optimization, it was proposed that the productivity of microalga-based processes can also be increased using various chemicals to trigger or enhance cell growth and accumulation of bioproducts. Herein, we summarized recent progresses in applying chemical triggers or enhancers to improve cell growth and accumulation of bioproducts in algal cultures. Based on their enhancing mechanisms, these chemicals can be classified into four categories：chemicals regulating biosynthetic pathways, chemicals inducing oxidative stress responses, phytohormones and analogues regulating multiple aspects of microalgal metabolism, and chemicals directly as metabolic precursors. Taken together, the early researches demonstrated that the use of chemical stimulants could be a very effective and economical way to improve cell growth and accumulation of high-value bioproducts in large-scale cultivation of microalgae.